Health services research in France: bridging the gap between academia and policymaking. (29th November 2020) - Spaak, Marine; Cipriano, Marion; Alla, François; Benamouzig, Daniel
Abstract: Background: — We aimed to identify the knowledge producers, the knowledge that they produce and the main areas of interest for health services research (HSR) in France, which is one of the priorities for public health research planning. Methods: — A two-phase approach comprising a bibliometric analysis and semi-structured interviews with 20 researchers and 13 staff members of public health bodies was used. Results: — In France today, interdisciplinary research teams are being organized in the main cities despite a lack of critical mass. The interviews showed that the term 'health services research' is vague with fuzzy boundaries between research, scientific expertise and evaluation. A keyword cluster analysis showed that French HSR is more hospital-centric compared to those countries that publish most frequently. The analysis also revealed a lack of research on methodological aspects. Conclusions: — We analyzed the structure of HSR in France and the specificity of the French publications in this field, compared with other countries. The results indicate the obstacles faced by researchers and decision-makers and offer insight into how these barriers may be removed.